Pengaruh Pendidikan Karakter terhadap Perkembangan Moral Siswa Sekolah Dasar - Mutia Shifana; Widya Sari; Hairun Nisak; Erika Sopia Ritonga; Wariyati Wariyati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine in depth the influence of character education on the moral development of elementary school students. Character education is a systematic effort to instill moral values ​​in students in order to form individuals who have noble character, are responsible, and are able to make ethical decisions in everyday life. In the context of elementary education, moral development is an important foundation for the formation of students' character and personality from an early age. This study uses a qualitative approach with a case study method implemented in one of the public elementary schools. Data collection techniques were carried out through observation of learning activities, in-depth interviews with teachers and students, and documentation of school activities related to character values. The results of the study showed that character education that is implemented in a planned and sustainable manner, both through positive habits, teacher role models, and integration of moral values ​​into subjects, is able to significantly encourage students' moral development. Students showed improvements in aspects of responsibility, honesty, respect, tolerance, and social concern. In addition, the active involvement of teachers and a supportive school environment also played a role in strengthening the internalization of these values ​​in students. This finding is in line with Lickona's (1991) view which emphasizes that character education not only forms good behavior, but also develops children's moral and emotional capacities holistically. Therefore, character education needs to be an integral and strategic part of the elementary school curriculum in order to form a young generation that is ethical, responsible, and has high integrity.